Kultura pracy. Pomiędzy niezależnością i powinnością = Work culture. Between independence and obligation - Wołk, Zdzisław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Work culture is a personality trait that results from personality dispositions and professional competence of individuals. Professional work has undergone numerous and radical changes and it still evolving. Today, in the conditions of market economy, it has a signi?cant impact on people and their lives. It facilitates ful?lling their needs; however, this entails high costs, namely the necessity to submit to the requirements of the employer and work environment. This limits the feeling of independence, all the more so that work entails numerous obligations.
Keywords: niezależność; powinność; kultura pracy; kodeks etyczny; etyka zawodowa; independence; obligation; work culture; code of ethics; professional ethics